Length-weight relationship and stomach contents of glass perchlet (Chanda nama) in Begnas Lake, Nepal - Thapa, Prativa; Basaula, Rajendra (Nepalese Journal of Zoology, 2025)
Elongated glass perchlet is a freshwater fish species in the Asiatic glassfish, family Ambassidae and order Perciformes. Length-weight relationship, condition factor, stomach contents and gastro-somatic index (Ga.SI) of Chanda nama were analyzed between February and April 2024 from the Begnas Lake of Pokhara Valley, Nepal. The total length was recorded in the range of 4.8 cm to 7.5 cm and total weight in the range of 0.81 gm to 5.52 gm. Similarly, the gut length and gut weight were in the range of 0.7 cm to 2 cm and 0.15 gm to 0.91 gm, respectively. Total length and body weight were positively correlated (R = 0.95, p < 0.05) whereas gut length and gut weight were negatively correlated (R = -0.19, p = 0.15). The value of growth exponential (b = 3.02) indicated positive allometric growth. The frequency of each of food items observed in stomach contents were scales (91.7%), insects (33.3%), zoobenthos (50%), eggs (41.7%), algae (25%), nostoc (36.7%) and unidentified materials (20%) throughout the study period. In conclusion, C. nama was lepidophagy. The Ga.SI value was used to determine feeding intensity and was found to be highest in the month of March and lowest in April. The present study suggested for further study about the C. nama and other fishes of the lake to know their status.